Cofactor Tail Length Modulates Catalysis of Bacterial F420-Dependent Oxidoreductases - Ney, Blair; Carere, Carlo R.; Sparling, Richard; Jirapanjawat, Thanavit; Stott, Matthew B.; Jackson, Colin J.; Oakeshott, John G.; Warden, Andrew C.; Greening, Chris (Frontiers in Microbiology, 2017)
F420 is a microbial cofactor that mediates a wide range of physiologically important and industrially relevant redox reactions, including in methanogenesis and tetracycline biosynthesis. This deazaflavin comprises a redox-active isoalloxazine headgroup conjugated to a lactyloligoglutamyl tail. Here we studied the catalytic significance of the oligoglutamate chain, which differs in length between bacteria and archaea. We purified short-chain F420 (two glutamates) from a methanogen isolate and long-chain F420 (five to eight glutamates) from a recombinant mycobacterium, confirming their different chain lengths by HPLC and LC/MS analysis. F420 purified from both sources was catalytically compatible with purified enzymes from the three major bacterial families of F420-dependent oxidoreductases. However, long-chain F420 bound to these enzymes with a six- to ten-fold higher affinity than short-chain F420. The cofactor side chain also significantly modulated the kinetics of the enzymes, with long-chain F420 increasing the substrate affinity (lower Km) but reducing the turnover rate (lower kcat) of the enzymes. Molecular dynamics simulations and comparative structural analysis suggest that the oligoglutamate chain of F420 makes dynamic electrostatic interactions with conserved surface residues of the oxidoreductases while the headgroup binds the catalytic site. In conjunction with the kinetic data, this suggests that electrostatic interactions made by the oligoglutamate tail result in higher-affinity, lower-turnover catalysis. Physiologically, we propose that bacteria have selected for long-chain F420 to better control cellular redox reactions despite tradeoffs in catalytic rate. Conversely, this suggests that industrial use of shorter-length F420 will greatly increase the rates of bioremediation and biocatalysis processes relying on purified F420-dependent oxidoreductases.